2022
DOI: 10.1002/adsu.202100453
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Porous Clay Heterostructures Modified with SiO2–ZrO2 Nanoparticles for the Valorization of Furfural in One‐Pot Process

Abstract: The layered structure of two smectites (montmorillonite and saponite) are modified by the insertion of SiO2–ZrO2 nanoparticles, with a Si/Zr molar ratio of 5, to form porous clay heterostructures (PCHs). These PCHs exhibit a clear improvement of the textural and acid properties in comparison to the starting clays, due to the formation of a pillared structure and the presence of Zr species, which provide an increase in the amount of Lewis acid sites. These materials are studied in one‐pot catalytic processes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…In the next step, FOL is etherified with the alcohol, used as a solvent, to form IpFE, requiring Lewis or Brönsted acid sites [26]. In this sense, it has been reported that other catalysts, such as Zr-based catalysts or zeolites, do not stop the reaction in FOL or IpFE, evolving towards other consecutive products in the one-pot process, in such a way that the IpFE yield with these catalysts is relatively low in comparison to the catalysts reported in this study [22,26,57]. Thus, it can be concluded that the use of Nb-based catalysts would favor the formation of alkylfurfuryl ethers.…”
Section: Catalytic Resultsmentioning
confidence: 59%
“…In the next step, FOL is etherified with the alcohol, used as a solvent, to form IpFE, requiring Lewis or Brönsted acid sites [26]. In this sense, it has been reported that other catalysts, such as Zr-based catalysts or zeolites, do not stop the reaction in FOL or IpFE, evolving towards other consecutive products in the one-pot process, in such a way that the IpFE yield with these catalysts is relatively low in comparison to the catalysts reported in this study [22,26,57]. Thus, it can be concluded that the use of Nb-based catalysts would favor the formation of alkylfurfuryl ethers.…”
Section: Catalytic Resultsmentioning
confidence: 59%
“…The peaks at 1630 and 3450 cm –1 represented the Si–OH bending and stretching vibration of hydrogen bonds due to the absorption of water on the PCH′s surface. In addition, it was difficult to examine any band in the −OH stretching, attributed to the occurred dehydroxylation in a phyllosilicate due to the calcination of the organic contents at 600 °C . The FTIR spectra of Ag/PCHs corresponded to porous clay heterostructures.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was difficult to examine any band in the −OH stretching, attributed to the occurred dehydroxylation in a phyllosilicate due to the calcination of the organic contents at 600 °C. 37 The FTIR spectra of Ag/PCHs corresponded to porous clay heterostructures. Moreover, there was no significant change in the chemical structure after coating the nano-silver on the porous clay heterostructure surface, and the increment of the contents of nano-silver did not affect the chemical structure of porous clay heterostructures.…”
Section: Characterization Of Nano-silver-coated Porous Claymentioning
confidence: 99%
“…10 HDTMA + monomers with alkyl chains C n H 2n+1 with n of 12− 20, corresponding to the length of ∼2 nm, are often employed as templates for the synthesis of PCHs. 11 Optimization of the second process, pillaring by templates between nanosheets, could be straightforward for raising the productivity of mesopores as well as their sizes since the nanometer-sized templates are removed to be mesopore sites. The pillaring effect and relevant enhancement of mesoporosity together with mesopore sizes have been thus studied focusing on the layer charges of base clay, 5 the chain length of surfactant, 12 the content of base clay, 13 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Porous clay nanoheterostructures (PCHs) are promising mesoporous silica-based materials synthesized adopting the above templating schemes. , The organic template substances participate in synthesizing PCHs as follows: substitution of interlayer cations by bulky organic cations to be a template, an addition of silicon alkoxide hydrolyzed around the template, filtration, washing of the obtained gel, and finally calcination to remove the template . HDTMA + monomers with alkyl chains C n H 2 n +1 with n of 12–20, corresponding to the length of ∼2 nm, are often employed as templates for the synthesis of PCHs . Optimization of the second process, pillaring by templates between nanosheets, could be straightforward for raising the productivity of mesopores as well as their sizes since the nanometer-sized templates are removed to be mesopore sites.…”
Section: Introductionmentioning
confidence: 99%